2013
DOI: 10.1007/s00431-012-1924-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of the quadrivalent meningococcal serogroups A, C, W-135 and Y tetanus toxoid conjugate vaccine (MenACWY-TT) in 2–10-year-old children: results of an open, randomised, controlled study

Abstract: In Europe, the introduction of monovalent meningococcal serogroup C (MenC) conjugate vaccines has resulted in a significant decline in MenC invasive disease. However, given the potential for strain evolution and increasing travel to areas of high endemicity, protection against additional serogroups is needed. In this study, the immunogenicity, measured by a serum bactericidal activity assay using rabbit complement (rSBA), and the safety of a quadrivalent meningococcal serogroups A, C, W-135 and Y tetanus toxoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 49 publications
1
26
1
4
Order By: Relevance
“…In the 6-10 years strata, using exploratory analysis, pain was reported more in the group receiving Men-PS (30%) compared to Men-ACWY-TT (20%) (P-value < 0.05). Moreover, in another phase III trial, involving children aged 2-10 years from Germany and France, solicited local AEs seemed to be more frequently reported than in the previously mentioned study 50 but similar to those reported by Knuf et al 42 Redness was the most common grade 3 solicited AE in both age strata. No statistically significant difference in local and general AEs was observed between those who received MenACWY-TT and those who received MenC-CRM with redness (35%) being the most common solicited AE in the 2-5 years strata and pain (44%) in the 6-10 years strata.…”
Section: Safety Profilementioning
confidence: 47%
See 3 more Smart Citations
“…In the 6-10 years strata, using exploratory analysis, pain was reported more in the group receiving Men-PS (30%) compared to Men-ACWY-TT (20%) (P-value < 0.05). Moreover, in another phase III trial, involving children aged 2-10 years from Germany and France, solicited local AEs seemed to be more frequently reported than in the previously mentioned study 50 but similar to those reported by Knuf et al 42 Redness was the most common grade 3 solicited AE in both age strata. No statistically significant difference in local and general AEs was observed between those who received MenACWY-TT and those who received MenC-CRM with redness (35%) being the most common solicited AE in the 2-5 years strata and pain (44%) in the 6-10 years strata.…”
Section: Safety Profilementioning
confidence: 47%
“…49 Again the immunogenicity of this vaccine in this same age group was evaluated in a phase III randomized study enrolling 415 subjects in Germany and France. 50 A single dose of MenACWY-TT was noninferior to MenC-CRM197 in terms of immunogenicity and vaccine response rates. 50 Moreover, MenACWY-TT was compared to another tetravalent conjugate vaccine MenACWY-DT in 1011 healthy 10 to 25 years old in a multi-centered phase II clinical trial in Canada and the United States.…”
Section: Immunogenicity Of Menacwy-ttmentioning
confidence: 99%
See 2 more Smart Citations
“…У участни-ков исследования наблюдали значительное повышение среднего геометрического титров (СГТ) бактерицидных антител. Во всех серогруппах у 86-100% участников при исходно неопределяемых значениях титров СБА (<1:8) была отмечена сероконверсия, определяемая как 4-крат-ное (или более) увеличение титров антител спустя 28 дней после вакцинации [5,6] .…”
Section: полисахаридные вакциныunclassified